Contribution of Lumbar Vertebral Magnetic Resonance Imaging to Diagnosis in Women with Osteoporosis - İrfan Atik; Seda Atik; Enes Gül; Sema Bulut (Galenos Yayinevi, 2022)
Objective:The aims of this study are to compare bone mineral densitometry and magnetic resonance imaging (MRI) findings in postmenopausal women diagnosed with osteoporosis and the investigation of the effectiveness of MRI in the diagnosis of osteoporosis.Materials and Methods:Forty female patients, 50 years of age or older who underwent lumbar MRI examination and were diagnosed with dual-energy X-ray absorptiometry (DEXA) osteoporosis were included in our study. Forty healthy women aged 20-29 years with lumbar MRI examinations were included in the control group. On sagittal T1-weighted (T1W) images of individuals in the patient and control groups signalto- noise ratio (SNR) was measured from L1-L4 vertebrae. To facilitate the diagnosis of osteoporosis, a quantitative score called the M-score was obtained using SNR values. The relationship between DEXA and the obtained SNR and M-score values were investigated.Results:In the patient group, median SNR values of L1, L2, L3, L4 vertebrae obtained from T1-weighted sequence was 57.49 (25.18-182.48), and they were 24.90 (7.40-41.70) in the control group. Receiver operating characteristics analysis was performed for L1, L2, L3, L4 vertebrae. The area under the curve for the mean value of L1-L4 vertebra was found to be 0.966 (p<0.001), and the 95% confidence interval was found 0.933-1.000. The mean SNR predictive value of L1-L4 was calculated as 33.45, and sensitivity for this value was found to be 90%, and specificity was found to be 90%. There was a negative correlation between lumbar MRI SNR-DEXA (p>0.05) and M score-DEXA (p>0.05).Conclusion:It has been concluded that L1-L4 vertebral SNR measurement in T1-weighted sequence in lumbar MRI can be used to distinguish osteoporosis patients from normal individuals. Thus, osteoporosis can be diagnosed without X-ray exposure.